2023
DOI: 10.3389/fendo.2023.1100453
|View full text |Cite
|
Sign up to set email alerts
|

Combination model of neutrophil to high-density lipoprotein ratio and system inflammation response index is more valuable for predicting peripheral arterial disease in type 2 diabetic patients: A cross-sectional study

Abstract: BackgroundNeutrophil/high-density lipoprotein (HDL) ratio (NHR), monocyte/HDL ratio (MHR), lymphocyte/HDL ratio (LHR), platelet/HDL ratio (PHR), systemic immune-inflammation index (SII), system inflammation response index (SIRI), and aggregate index of systemic inflammation (AISI) have been recently investigated as novel inflammatory markers. Herein, the correlation was investigated between these inflammatory biomarkers and peripheral arterial disease (PAD) in type 2 diabetes mellitus (T2DM) patients.MethodsIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Recently, prognostic haematological inflammatory parameters, including the neutrophil/lymphocyte ratio (NLR), monocyte/lymphocyte ratio (MLR), and platelet/lymphocyte ratio (PLR), have been widely described [ [25] , [26] , [27] ]. These parameters are easily measured from CBC indices and provide prognostic values for systemic inflammation [ [25] , [26] , [27] ]. However, no previous study has investigated the impact of cupping on these inflammatory parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, prognostic haematological inflammatory parameters, including the neutrophil/lymphocyte ratio (NLR), monocyte/lymphocyte ratio (MLR), and platelet/lymphocyte ratio (PLR), have been widely described [ [25] , [26] , [27] ]. These parameters are easily measured from CBC indices and provide prognostic values for systemic inflammation [ [25] , [26] , [27] ]. However, no previous study has investigated the impact of cupping on these inflammatory parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings implied that cupping therapy is associated with decreased secretion of proinflammatory markers such as interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) [ 31 , 32 ]. The neutrophil/lymphocyte ratio (NLR), monocyte/lymphocyte ratio (MLR), and platelet/lymphocyte ratio (PLR) have been recently suggested as diagnostic and prognostic factors for systemic inflammation [ [25] , [26] , [27] ]. NLR is an inflammatory marker and measures the ratio between neutrophil counts (associated with innate immunity) and lymphocyte counts (linked to adaptive immunity) in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies demonstrated that biomarkers derived from peripheral blood cells, such as the neutrophil to HDL-C ratio [ 27 , 36 , 48 ], monocyte to HDL-C ratio (MHR) [ 32 , 34 , 49 , 50 ], lymphocyte to HDL-C ratio (LHR) [ 27 , 35 , 36 , 37 ], platelet to HDL-C ratio (PHR) [ 27 , 39 , 51 ], System Inflammation Response Index (SIRI) [ 25 , 26 , 31 , 49 , 50 ], Systemic Immune-Inflammation Index (SII) [ 25 , 28 , 31 , 33 ], and Aggregate Index of Systemic Inflammation (AISI) [ 27 , 52 , 53 ], can be used to detect and predict the presence and severity of systemic inflammatory processes, including cardiovascular diseases and MetS.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, increased levels of inflammatory biomarkers (e.g., Interleukin-6, Tumor Necrosis Factor-alpha, C-reactive protein, the neutrophil to lymphocyte ratio, and the platelet to lymphocyte ratio) have been correlated with both obesity and MetS [ 20 , 21 , 22 , 23 , 24 ]. Furthermore, new hematological parameters related to HDL-C and complete blood cell profiles have been proposed as novel inflammatory biomarkers [ 25 , 26 , 27 , 28 , 29 , 30 ]. These include the monocyte/HDL-C ratio (MHR), lymphocyte/HDL-C ratio (LHR), neutrophil/HDL-C ratio (NHR), platelet/HDL-C ratio (PHR), System Inflammation Response Index (SIRI), Systemic Immune-Inflammation Index (SII), and Aggregate Index of Systemic Inflammation (AISI).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated NHR value is generally considered as an indicator of chronic in ammation and lipid metabolism disorder [19]. There have been several disorders that have been linked to NHR, such as coronary heart disease [20], diabetes [21], mental illness [22], and…”
Section: Introductionmentioning
confidence: 99%